Dynamic control of welding current and welding time to investigate ultimate tensile strength of miab welded T11 tubes. (April 2018) - Dhivyasri, G.; Rahul, S.G.; Kavitha, P.; Arungalai Vendan, S.; Ramesh Kumar, K.A.; Gao, Liang; Garg, Akhil
Highlights: Problem on influence of welding current and time on depth of MIAB is undertaken. Dynamic Double PI-PID Scheme is proposed to solve the problem. Comparative study is conducted based on Zeigler-Nichols method and Auto tuning. Experimental values and the results of developed control scheme show good agreement. Abstract: This study undertakes the objective of investigating the influence of welding current and welding time on the depth of penetration in Magnetically Impelled Arc Butt Welding classified under solid-state welding process. It is essential to create a parametric window for optimizing the range of process parameters that yields good mechanical properties expressed in terms of Ultimate Tensile Strength. This is attributed to the implications on the depth of penetration and the associated metallurgical properties. For this study, T11 tubes of 48–54 mm outer diameter with a thickness of 6.6–7 mm are adopted considering its versatile applicability in boiler and boiler accessory components. MIAB welding equipment available at welding research institute, BHEL is employed for this study. Welding current which is the key parameter that is segregated into three sections based on its differing implications on the weldment. On similar lines, the time zone is also divided into four sections. Each of them reveals significant effect on the joint properties. The welded specimens are subsequently subjected to tensile strength on a universal tensile testing machine. This is followed by development of a Double PI-PID control scheme to accomplish the improved system performance by operating it within the optimized range. A comparative study is presented on tuning of the developed controller by the conventional Zeigler-Nichols method and Auto tuning. The developed controller is then validated by comparing its performance with conventional PID controller. The stability analysis following the control scheme evaluation illustrates the accomplishment of persistent reliability and repeatability. The experimental values and the results of developed control scheme show good agreement with each other while also establishing its parametric control credibility. This study which is a conclave of mechanical/electrical and control engineering is expected to create better controllability and automate-ability there by facilitating the achievement of good weld in terms of strength and quality.